Cervical Spine Trauma - Dahlan, Rully Hanafi; Ompusunggu, Sevline Estethia; Baselim, Ismail M.; G., Yustinus Robby B. (Talenta Universitas Sumatera Utara, 2019)
Cervical trauma is a serious condition, that may cause permanent disability or even death. Cervical trauma occurs in 2-7% of blunt trauma patients. In Europe, the incidence of cervical trauma is approximately 9-17/100,000 annually,. The most common mechanisms of injury causing cervival trauma are traffic accidents and falls, which the most commonly injured vertebra is vertebral C2 (axis). Diagnostics of cervical trauma are based on good clinical assessment and prompt radiological imaging. Several patient groups, such as the elderly and patients with traumatic brain injury are highly susceptible to cervical trauma. The diagnostics of cervivcal trauma remain challenging for clinical practitioners and failure to diagnose cervical trauma in acute care may have serious consequences.